Analogy and feminism in "Trifles" by Susan Glaspell - Rodríguez Pequeño, Javier (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paper analyzes the drama in one act Trifles, by Susan Glaspell, attending to its metaphorical procedures, produced thanks to the principles of analogy and transferability. These procedures allow the author to make a deep and critical reflection on aspects such as the historical tyranny that the patriarchy has exercised over women around the world and in all eras.
Keywords: Susan Glaspell; Trifles; metaphor; analogy; feminism